Pengaruh Coaching Rasa-Tirta Terhadap Kemampuan Guru dalam RPP Pembelajaran Berdiferensiasi - Rini, Dyah Sinto (Jurnal Didaktika Pendidikan Dasar, 2024)
This school action research aims to improve teachers’ abilities in compiling and implementing learning implementation plans (RPP) or teaching modules (MA) for differentiated learning using the ’Sweet Inspiration’ media combined with RASA-TIRTA coaching. The subjects of this research were six teachers from different schools. This research was carried out through the planning, implementation, observation and reflection stages. Data collection techniques include interviews, product assessment, observation and discussion. The results of the research show that the average achievement value for the differentiated learning RPP component indicators in cycle II was 91.11%, including the very good category. The average achievement indicator value for implementing lesson plans in class was 88.53%. So, the target for achieving indicator values has been achieved. It can be concluded that the ’Sweet Inspiration’ media combined with RASA-TIRTA coaching (a) can improve teachers’ abilities in compiling and implementing differentiated RPP learning and (b) makes teachers feel comfortable discussing, learning and sharing during this research process at assisted junior high schools in Tangerang City.